Estudos de Adsorção de Xilenos em Zeólita Beta: Avaliação de Seletividade e Difusividade - Lima Júnior, José Wilson Vieira (2018)
The xylenes (C8 aromatics) are isomers compounds obtained from the petroleum fractions. Separation of C8 aromatics mixtures is an important issue in the petrochemical industry. The adsorption process presents as the best alternative in the separation of these isomers. In this study, the adsorption selectivity of xylenes on Beta zeolite was investigated, initially, through the headspace chromatography technique. The headspace technique was used to study the thermodynamic equilibrium in adsorption processes. The selectivity was investigated in binary and multicomponent systems of xylenes (ortho-, meta- and para-xylene and ethylbenzene) in different molar ratios and temperatures (40, 60 and 80 °C). In binary systems (ortho- and para-xylene), a para-selectivity character (αpx/ox> 3) was observed in all molar ratios evaluated. In the multicomponent mixture, the selectivity was higher for the ethylbenzene and para-xylene in relation to the other isomers. In the second part of this study, the kinetic parameters of the C8 aromatics and n-octane were obtained by Zero Length Column method (ZLC). This technique allows evaluating the intracrystalline diffusion of hydrocarbons in porous materials, having the advantage of eliminating heat and mass transfer external resistance and the axial dispersion. The diffusivity values for the components under study were in the order of 10-15 m2 s-1 in the temperatures evaluated (80, 100 and 120 °C). The results showed that Beta zeolite has a potential application for the separation of xylenes in mixtures with para-xylene or ethylbenzene.